Green emitting rare earth Gd2O3:Tb3+ nanoparticles for rapid imaging of latent fingerprint. (4th February 2021) - Maalej, Nabil M; Qurashi, Ahsanulhaq; Bennour, Ines; Haddada, Lamia Rzouga; Shaikh, M. Nasiruzzaman; Ilyas, Muhammad; Essoukri Ben Amara, Najoua; Maalej, Ramzi; Gondal, Mohammad A
Abstract: A series of green emitting Gd2 O3 :Tb 3+ (Tb: 0%–10% mol) nanoparticles (NP) were synthesized using the hydrothermal method, then characterized and evaluated for latent fingerprint visualization. X-ray diffraction study (XRD) revealed a cubic structure of the nanoparticles and the total incorporation of the terbium in the Gd2 O3 matrix. Field Emission-Scanning Electron Microscopy (FESEM), Energy Dispersive x-ray Spectrometry (EDX) and Transmission Electron Microscopy (TEM) were used to study the morphology and the elementary composition of the NP. Photoluminescence (PL) studies showed strong green emission around 540 nm due to the transition 5 D4  →  7 F5 . The luminescence color of the synthesized NP was characterized by the CIE 1931 chromaticity diagram. The potential use of the NP powders for the visualization of latent fingerprint under UV irradiation was assessed on various substrates. The latent fingerprint images revealed by the Gd2 O3 :Tb 3+ NP powders are clear enough to extract and analyze reliable fingerprint features. The fingerprint quality was evaluated using three fingerprint quality assessment metrics and by extracting and measuring the visibility of the minutiae. The experimental results show very good quality images of the latent fingerprint acquired using the Gd2 O3 :Tb 3+ NP and yield good minutiae extraction.